2017
DOI: 10.1182/blood-2016-07-727719
|View full text |Cite
|
Sign up to set email alerts
|

Association among sickle cell trait, fitness, and cardiovascular risk factors in CARDIA

Abstract: Key Points• SCT status is not significantly associated with longitudinal changes in fitness among African Americans.• SCT status is not an independent risk factor for hypertension, diabetes, or metabolic syndrome among African Americans.The contribution of sickle cell trait (SCT) to racial disparities in cardiopulmonary fitness is not known, despite concerns that SCT is associated with exertion-related sudden death. We evaluated the association of SCT status with cross-sectional and longitudinal changes in fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…However, these individuals are susceptible to some environmental conditions including strenuous sports such as fitness, insufficient fluid intake, alcohol use, and low oxygen pressure . Individuals with Hemoglobin S trait are claimed to be under risk for thromboembolic events, rhabdomyolysis, cardiovascular system diseases, and sudden death …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these individuals are susceptible to some environmental conditions including strenuous sports such as fitness, insufficient fluid intake, alcohol use, and low oxygen pressure . Individuals with Hemoglobin S trait are claimed to be under risk for thromboembolic events, rhabdomyolysis, cardiovascular system diseases, and sudden death …”
Section: Discussionmentioning
confidence: 99%
“…The heterozygous trait (sickle cell trait) is common among Afro‐Americans, Asians, Indians, Latin Americans, Mediterranean, and Middle East communities . Individuals with sickle cell trait are suggested to be susceptible to health‐related problems such as venous thrombosis, cardiovascular diseases, sudden death, and rhabdomyolysis despite hematological parameters being within normal ranges . Some of the healthy volunteers are naturally anticipated to be hemoglobin S trait, particularly in the above mentioned regions.…”
Section: Introductionmentioning
confidence: 99%
“…While individuals with SCT typically remain asymptomatic and do not suffer significant morbidity, these individuals are at risk of having a child with SCT or SCD (Centers for Disease Control and Prevention; Liem et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…While sickle cell trait (SCT) has been considered an essentially asymptomatic and benign condition associated with increased survival from malaria infection and normal life expectancy, recent studies have suggested that it may be associated with some complications of sickle cell disease (SCD) (Key et al , ) while other studies revealed no impact on baseline health and fitness (Liem et al , ). Individuals with SCT carry only a single copy of the mutated allele encoding the variant of haemoglobin that is known to cause SCD; the presence of normal β globin subunits within circulating red blood cells (RBCs) is protective against haemoglobin polymerization and RBC sickling.…”
mentioning
confidence: 99%